2016
DOI: 10.3389/fnbeh.2016.00161
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Midbrain NMDA Receptor Blockade: From Enhanced Reward and Dopamine Inactivation

Abstract: Glutamate stimulates ventral midbrain (VM) N-Methyl-D-Aspartate receptors (NMDAR) to initiate dopamine (DA) burst firing activity, a mode of discharge associated with enhanced DA release and reward. Blockade of VM NMDAR, however, enhances brain stimulation reward (BSR), the results can be explained by a reduction in the inhibitory drive on DA neurons that is also under the control of glutamate. In this study, we used fast-scan cyclic voltammetry (FSCV) in anesthetized animals to determine whether this enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Both effects could be associated with a reduction in the release of DA from the nucleus accumbens since this decrease can affect both reward and motor function [ 51 ]. It has been shown that electrical and optical stimulation of DR neurons produces an increase in DA cell firing and DA phasic release [ 2 , 15 , 52 ] via glutamatergic DR efferents to the VTA [ 1 , 2 , 20 ]. Substantial reduction in the GluN2C input likely decreases glutamatergic excitability in DA neurons, reducing the overall DA release in terminal areas.…”
Section: Discussionmentioning
confidence: 99%
“…Both effects could be associated with a reduction in the release of DA from the nucleus accumbens since this decrease can affect both reward and motor function [ 51 ]. It has been shown that electrical and optical stimulation of DR neurons produces an increase in DA cell firing and DA phasic release [ 2 , 15 , 52 ] via glutamatergic DR efferents to the VTA [ 1 , 2 , 20 ]. Substantial reduction in the GluN2C input likely decreases glutamatergic excitability in DA neurons, reducing the overall DA release in terminal areas.…”
Section: Discussionmentioning
confidence: 99%
“…One further possibility is that continuous electrical stimulation of the VTA may induce a relatively rapid depolarization block (DB) similar to chronic antipsychotic treatments that, in turn, decrease tonic DA levels in the NAcc ( Lane and Blaha, 1987 ; Grace et al, 1997 ; Boye and Rompre, 2000 ; Hernandez et al, 2016 ). These hypotheses can be investigated by further studies using other pharmacological tests and measuring techniques such as amperometry.…”
Section: Discussionmentioning
confidence: 99%
“…Both effects could be associated with a reduction in the release of DA from the nucleus accumbens since this decrease can affect both reward and motor function [45]. It has been shown that electrical and optical stimulation of DR neurons produces an increase in DA cell firing and DA phasic release [2,15,46] via glutamatergic DR efferents to the VTA [1,2,20]. Substantial reduction in the GluN2C input likely decreases glutamatergic excitability in DA neurons, reducing the overall DA release in terminal areas.…”
Section: Discussionmentioning
confidence: 99%